Pengaruh Suhu terhadap Stabilitas Larutan Vitamin C (Acidum ascorbicum) dengan Metode Titrasi Iodometri - Putu Vellina Damayanti; I Gusti Ngurah Jemmy Anton Prasetia (Universitas Muhammadiyah Klaten, 2021)
The stability of pharmaceutical preparations is a very important criterion for a good production result where the stability of the drug can be influenced by external factors such as temperature. The sample used was a vitamin C solution with another name Acidum Ascorbicum (ascorbic acid) with a molecular formula of C6H8O6 and a molecular weight of 176.13 g / mol where the solution was tested for stability using the Iodometric titration method. Based on the calculation results, the vitamin C levels obtained in sample I (without heating) were 0.16644% w/v, in sample II (heating for 30 minutes) was 0.06376% w/v, in sample III (heating for 60 minutes) which is 0.15675% w/v, in sample IV (heating for 90 minutes) is 0.15288% w/v, and in sample V (heating for 120 minutes) is 0.16063% w/v. Thus, an increase in temperature can accelerate the occurrence of reactions that can disturb a substance's stability. Vitamin C The longer the heating time, the more vitamin C is oxidized, so that the remaining vitamin C levels will decrease due to the decomposition process.